Pharmaceutical and biomedical project management in a changing global environment - Babler, Scott D. (Hoboken, N.J. : Wiley, 2010)
"This book explores some of the critical forces at work today in the complex endeavor of pharmaceutical and medical product development. Applying a structured project management framework enables companies to select and allocate the appropriate people and resources to achieve successful outcomes. The book presents chapters addressing selected issues written by experienced professionals grappling with these problems every day. Such coverage provides real-world examples of contemporary problems and their solutions"--Provided by publisher.
(Publisher-supplied data) 1: Project Leadership for Biomedical Industries/ Scott D. Babler -- 2: Medical Devices ? Components, Systems, and their Integration / Dennis F. Marr -- 3: The Role of Project Management in the Development of In Vitro Diagnostics / David Kern and Diane M. Ward -- 4: Drug Development Project Management / Dirk L. Raemdonck and Bradford A. Burns -- 5: Outsourcing of Project Activities / Jonathan D. Lee and Trisha Dobson -- 6: The Unique Aspects of Alliance Projects / Andrew S. Eibling -- Case Study: Management of Outsourcing for Biomedical Companies / Jeffery W. Frazier, Jennifer A. Hewitt and Andy Myslicki -- 7: A Roadmap for Successful Technology Transfers / Nipun Davar, Sangita Ghosh, Nandan Oza -- 8: Challenges for the Team Leader of Multifunctional Product Teams in an International Environment / Hartwig Hennekes -- 9: Lessons Learned from Inter-Organizational Collaboration Projects / Andrea Jahn -- 10: Clinical Trials and Project Management / Scott E. Smith, Carol A. Connell and Dirk L. Raemdonck -- 11: Role of Project Management in Quality Planning and Functions Throughout the Product Lifecycle / Thomas Dzierozynski and Ian Fleming -- 12: Regulatory Strategies and Submissions in an International Product Environment / Louise Johnson -- 13: Risk Management - A Practical Approach / Courtland R. LaVallee -- 14: Managing Successful Product Portfolio Creation and R&D Pipelines / Sue E. Steven -- 15: Effective Strategies for Project Resource Planning and Utilization / Eduardo Rojas and Scott D. Babler -- 16: Stage Gate Product Development Processes and Lifecycle Management / Karen E. Coulson -- 14: Managing Successful Product Portfolio Creation and R&D Pipelines / Sue E. Steven -- 15: Effective Strategies for Project Resource Planning and Utilization / Eduardo Rojas and Scott D. Babler -- 16: Stage Gate Product Development Processes and Lifecycle Management / Karen E. Coulson.
Includes index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Project management; Pharmaceutical industry; Medical instruments and apparatus industry; Electronic books